MODEL TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA TEMA CITA-CITAKU KELAS IV SD N 6 SUWAWAL - Qoriati Mushafanah, Novita Rahmanika Yan (Universitas PGRI Semarang, 2014)
This study is based on learning are less involved in learning activities among students, learning is done more emphasis towards the cognitive load and the number of students studying to be learned. A large load of learning and classroom learning activities pose little memorable learning monotonous and boring. The problems revealed in this study is there any difference in learning outcomes between students who use the model Teams Games Tournament (TGT) with students using the conventional model of my dream theme fourth grade N 6 Suwawal? The purpose of this study was to determine whether there is difference in learning outcomes between students who use the model Teams Games Tournament (TGT) with the conventional model of my dream theme fourth grade N 6 Suwawal. This research is True Experimental Design. The population in this study is a fourth grade student n 6 Suwawal. Samples taken consists of two classes of grade IV A numbered 19 students, and class IV B amounts to 20 students by using a sampling technique saturated. The study design used was a posttest-only control group design. The data collection method used was a test, documentation, and observation. The instrument used is an evaluation test that has been on test validity, reliability, distinguishing features and the difficulty level. The collected data was then analyzed using the t test, which previously tested for normality and homogeneity. The results show the average results of the experimental study class for an average of 73.75 and a control class learning outcomes by 67.42. Based on the results shown by the average of the results of learning, the two classes are normally distributed and the two homogeneous groups. Then on ttest analysis obtained t of 3.10 while ttable with n1 + db + n2-2 = 20 19-2 = 37 and a significance level of 0.05 by 2.02. Because tcount> ttable ie 3.10> 2.02 then Ho is rejected and Ha is accepted or it can be said that there are differences in learning outcomes between students who use the model Teams Games Tournament (TGT) to the student learning outcomes of students who use the conventional model of my dream theme fourth grade N 6 Suawawal. Differences in study results showed the influence of the model Teams Games Tournament (TGT) to the student learning outcomes theme my goal fourth grade N 6 Suwawal. Thus the suggestion that teachers should be able to convey researchers to use the learning model Teams Games Tournament (TGT) in learning, especially learning thematic Terintegratif.